The Influence of Product Quality and After Sales Services on Customer Satisfaction in Mahir Residence Sukabumi - Erry Sunarya; Maun Jamaludin (Publindo Akademika, 2022)
The problem found at Mahir Residence Sukabumi is the emergence of consumer dissatisfaction with the products produced by the company. The problem is thought to have occurred due to poor product quality and less than optimal after-sales service. This study aimed to determine the magnitude of the effect of product quality and after-sales service on consumer satisfaction. The research method used is a descriptive and associative method with the research design is a causality and verification type of investigation. The data analysis technique uses multiple correlation coefficients, multiple linear regression, coefficient of determination, and hypothesis testing with the F test. The most dominant variable affecting consumer satisfaction in this study is product quality. Based on the results of the study, the correlation between product quality and after-sales service was 0.437, the magnitude of the effect of product quality on consumer satisfaction was 31.9%, the magnitude of the effect of after-sales service on consumer satisfaction was 22.3%, and the magnitude of the influence of product quality and after-sales service selling to consumer satisfaction together by 43.7% while the remaining 56.3% is influenced by other factors that are not included in this study. From the results of this study, it can be seen that product quality and after-sales service can affect consumer satisfaction.